Peningkatan Nilai Produk Melalui Perijinan PIRT, Sertifikasi Halal, dan Digital Marketing pada Produk Usaha Mahasiswa STIE Gentiaras - Fanny Sumaedi Rabianto; Maria Kristiningsih (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The high consumer interest in food makes culinary businesses play a crucial role in meeting consumer purchasing interest in culinary. This is a crucial concern and task for all parties, both the government and food producers, to maintain the safety of the food they produce. Both in terms of nutrition, hygiene, safety, halal certification, and so on must be a serious concern for producers. One of the government's programs to ensure food products are safe for public consumption is by issuing distribution permits in the form of PIRT (home industry food) permits and Halal Certification, which are official guarantees from the government, so that food products can be distributed and are safe for consumption by all consumers. PIRT is issued through a supervisory body, namely the Health Office located in a Regency. Along with this, various opportunities to improve marketing performance arise through the marketplace platform. This community service approach uses an empowerment approach to the benefits of PIRT, Halal Certification and digital marketing through the marketplace platform to increase consumer trust in products and marketing performance. Through this service, the product value increases, by obtaining PIRT permits and Halal Certification, and the STIE Gentiaras student product has a wider marketing reach through the marketplace platform.